KONTRIBUSI BAZNAS MELALUI PEMBERIAN MODAL BISNIS TERHADAP PEREKONOMIAN MASYARAKAT MISKIN DI KABUPATEN KEPULAUAN MERANTI - IMAM FAKHRUDDIN (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is motivated by the problems that exist in BAZNAS Meranti Islands Regency which has an agenda to distribute productive zakat to the poor. With this program, BAZNAS of Meranti Islands Regency hopes that people who receive productive zakat can be independent and can develop businesses to generate income and be able to meet their daily needs. However, based on the information obtained by the researcher, the mechanism used is unique, namely the recipient of zakat as business capital must save in the bank until it reaches the same amount as the capital he receives. The theory used in this study is the concept of zakat in general, productive zakat and the concept of the poor as mustahiq. This research is a field research (Field Research) and the type of research is qualitative. The results of this study are the mechanism for implementing the productive meranti program of BAZNAS in Meranti Islands Regency, which is adjusted to the condition of the community and the ability of existing resources, both from determining mustahiq, the nominal amount of assistance and also coaching or supervision. The contribution of BAZNAS to the economy of the poor in Meranti Islands Regency through the productive meranti program by providing business capital has been quite good, although so far many have failed in running their businesses. However, BAZNAS's efforts have greatly helped the poor in terms of capital for their businesses. It only takes a good process and management to be able to maximize the program.